Basic Arithmetic Learning through Math Online Games for Elementary School Students during the Pandemic - Lathifah, Nida Nabilah; Maryanti, Rina (Universitas Pendidikan Indonesia (UPI), 2021)
The purpose of this study is whether online math games can be one of the basic arithmetic lessons during the online learning process during the Covid-19 Pandemic. To support the research, we use an experimental research method, which is to try out a lesson using an online math game application to 10 4th grade elementary school students for 2 days. While the approach used in this study is quantitative. The results show that there are still many students who are not fluent in working on basic arithmetic problems before playing math online games. So that learning through online math games is very helpful for students in improving their numeracy skills. This is because as long as students play the game, students can continue to hone their numeracy skills. Thus, the student who gets a final score of more than 70 at the time of the post-test increase to 50% compared to the time of the pre-test which is only 40%. Therefore, it is clear that online math games can be a method of learning basic arithmetic to improve students' numeracy and literacy levels.